Human rights for refugees: enhancing sustainable humanitarian supply chain to guarantee a health environment in refugee settlements - Alexandre Augusto Karl; Julia Scholz Karl (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – Despite global efforts for environmental protection, there is a gap in the literature about the contributions of a sustainable humanitarian supply chain (SHSC) to the promotion of human rights in refugee settlements. In this context, this study investigates how the generation of sustainability in the humanitarian supply chain (HSC) acts as an instrument for guaranteeing the human rights for refugees. Design/methodology/approach – A literature review was conducted to identify the state of the art and research challenges as well as an analysis of international law documents related to refugees, international human rights law and environmental protection, and a critical study of sustainable initiatives already taken by international organizations and humanitarian agencies in refugee camps. Findings – As a result, ensuring human rights in refugee camps is directly related to the development of a SHSC that contributes without deviation to the enjoyment and exercise of human rights by preserving the local environment. Originality/value – This study offers a literature review and discusses the generation of sustainability in refugee camps and its relationship with human rights protected by rules of international law. Aspects such as the circular humanitarian supply chain are for the first time discussed, introducing the circular economy to refugee settlements.